Nd-Fe-B magnets under electron irradiation with the energy of 23 MeV - Bovda, V.A.; Bovda, А.М.; Guk, I.S.; Dovbnya, A.N.; Lyashchenko, V.N.; Mytsykov, A.O.; Onishchenko, L.V.; Каndybei, S.S.; Repikhov, О.А. (Вопросы атомной науки и техники, 2020)
Four Nd-Fe-B magnets underwent irradiation under 23 MeV electron beam. Nd-Fe-B magnets were magnetized to the technical saturation in the magnetic field of 3.5 T before electron treatment. Two Nd-Fe-B samples (1 and 2) were exposed to the direct electron beam with the energy of 23 MeV. Sample 2 was shielded by tungsten converter. The thickness of the tungsten converter was 4.72 mm. The absorbed dose for the samples was 16 GRad. Sample 3 was subjected to bremsstrahlung of electron irradiation with the energy of 23 MeV. Sample 4 was used as a reference sample for calibration and control measurements. While magnetic flux of sample under direct electron beam of 23 MeV was changed significantly, sample 2 showed the change of magnetic flux to a less degree. Magnetic performance of sample 3 corresponded closely to the initial state.